Urgensi Omnibus Law (Undang-Undang Cipta Kerja) Terhadap Hak Masyarakat Adat di Wilayah Pesisir - Dolfries J Neununy (Balobe Law Journal, 2021)
Introductioan: Substantial application of the Omnibus Law (Cipta Kerja) for the rights of indigenous peoples in coastal areas.Purposes of the Research: Reviewing and analyzing the impact of the Copyright Act on indigenous peoples in coastal areas.Methods of the Research: The research was conducted through normative legal research with a political approach to review and analyze legislation or other legal materials related to the Urgency of Omnibus Law on the Rights of Indigenous Peoples in coastal areas.Results of the Research: The presence of the Omnisbus Law will have a positive impact on the community from the aspect of legal knowledge that people belonging to the scientific community can understand the purpose of the government to implement the Omnisbus Law but from the other side the ordinary people who are in coastal areas and remote rural areas do not understand well the application of the Omnisbus Law so that protection is important.